2019
DOI: 10.12659/msm.916667
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Uric Acid Levels Promote Vascular Smooth Muscle Cells (VSMC) Proliferation via an Nod-Like Receptor Protein 3 (NLRP3)-Inflammasome-Dependent Mechanism

Abstract: BackgroundHyperuricemia has a pathogenic role in the development of hypertension and other cardiovascular diseases (CVD). Uric acid has been reported to activate Nod-like receptor protein 3 (NLRP3)-inflammasome and alter vascular smooth muscle cells (VSMC). However, the potential mechanisms underlying this association are still not understood. The aim of this study was to investigate the role and potential mechanisms of uric acid in proliferation of VSMC.Material/MethodsCell Counting Kit-8 (CCK-8) proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Studies by Wang et al report that UA can activate nod-like receptor protein 3 (NLRP3) inflammasomes and damage mitochondria, resulting in cellular damage of H9c2 cells ( Wang et al, 2018 ). In addition, several studies also show that UA activates the NLRP3 inflammasome and induces interleukin-1β (IL-1β) release in a variety of cells, including monocytes, macrophages, vascular smooth muscle cells, and endothelial cells ( Martinon et al, 2006 ; Matias et al, 2015 ; Alberts et al, 2019 ; Kim et al, 2019 ; Li et al, 2019 ; Yin et al, 2019 ). The molecular mechanism of UA-induced NLRP3/IL-1 β activation is through NF-κB activation and mitochondrial ROS (mROS) ( Figure 2 ).…”
Section: Ua and Its Related Molecular Mechanismmentioning
confidence: 99%
“…Studies by Wang et al report that UA can activate nod-like receptor protein 3 (NLRP3) inflammasomes and damage mitochondria, resulting in cellular damage of H9c2 cells ( Wang et al, 2018 ). In addition, several studies also show that UA activates the NLRP3 inflammasome and induces interleukin-1β (IL-1β) release in a variety of cells, including monocytes, macrophages, vascular smooth muscle cells, and endothelial cells ( Martinon et al, 2006 ; Matias et al, 2015 ; Alberts et al, 2019 ; Kim et al, 2019 ; Li et al, 2019 ; Yin et al, 2019 ). The molecular mechanism of UA-induced NLRP3/IL-1 β activation is through NF-κB activation and mitochondrial ROS (mROS) ( Figure 2 ).…”
Section: Ua and Its Related Molecular Mechanismmentioning
confidence: 99%
“…Furthermore, hyperuricemia is related to hypertension, coronary heart disease, stroke, diabetes, obesity, and metabolic syndrome [1][2][3][4][5]. The mechanistic role of UA in several comorbidities suggested that UA stimulates vascular smooth muscle proliferation and oxidative stress [6]. Hyperuricemia is associated with endothelial dysfunction by inducing inhibition of nitric oxide production [7].…”
Section: Introductionmentioning
confidence: 99%
“…KEGG pathway analysis showed that phagosomes are the most enriched pathways in upregulated genes, and drug metabolism-cytochrome P450 is the most enriched pathway in downregulated genes. Among the significantly enriched pathways, the NOD-like receptor (NLR) pathway, cell adhesion molecule (CAM), and the NF-kappa B (NF- κ B) signaling pathway are potentially closely related to AAA pathogenesis [ 23 25 ]. It was considered that these lncRNAs might participate in the biological process of SMAD protein signal transduction and immune response in AAA progression via mediating the above significantly enriched pathways.…”
Section: Discussionmentioning
confidence: 99%